RELATIONSHIP OF NUTRITION STATUS WITH METABOLIC SYNDROME PHENOMENON IN AROSBAYA DISTRICT, SABUH VILLAGE BANGKALAN-MADURA - Wati, Popy Mega; Ernawati, Ernawati (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2016)
Obesity has become a global problem in the world and showed a sharp upward trend. Coincide with the increasing in obesity, also known as metabolic syndrome. Metabolic syndrome (MS) is a complex metabolic disorder caused by an increasing in obesity. Several Â groups of studies suggest that obesity, insulin resistance, dyslipidemia and hypertension areÂ the major component MS. Based on data from Public Health Center in Arosbaya-Bangkalan Madura, hypertension, diabetes mellitus, and disorders of lipid metabolism showed a fairly high number of patients in each year. The aim of this research was to analyze the relationship of nutrition status with metabolic syndrome phenomenon in Arosbaya District, Sabuh Village Bangkalan-Madura. This research was an observational study with cross sectional study approach Chi-square statistical test. The samples used were 70 people who are society of Sabuh Village. Variable consists of a Body Mass Index (BMI) as independent variables, and components of the metabolic syndrome that includes waist circumference, fasting blood glucose, triglycerides as the dependent variable. The results showed a significant relationship between nutrition status and some components of the metabolic syndrome (Î± <0.05). From the analysis it can be concluded that nutrition status has an influence on the phenomenon of metabolic syndrome. Adopting a healthy lifestyle is one of the prevention of obesity and other comorbidities.